Implementation of Energy Harvesting Technology for Sustainable Infrastructure Projects - Timotius Alfanov; Oei Fuk Jin (Universitas Muhammadiyah Purwokerto, 2025)
Digital construction has become an important strategy in promoting the Sustainable Development Goals (SDGs) set by the United Nations, especially in the context of infrastructure development. The purpose of this research is to discuss the development of Energy Harvesting (EH) technologies that have been investigated in infrastructure to date. By utilizing energy in the surrounding environment, EH technology offers great potential in reducing carbon emissions generated by infrastructure systems. This study employs the Systematic Literature Review (SLR) method, involving a structured process of literature search in the Scopus database, selection based on abstracts and content relevance, and in-depth analysis of 27 qualified articles. This research discusses five of the most common EH technologies, namely photovoltaic, piezoelectric, thermoelectric, Wind Energy Conversion System (WECS), and Wind Energy Converter (WEC) technologies. Each technology was evaluated based on its application in infrastructure with a focus on the efficiency and effectiveness of the application of the technology. The results indicate that Photovoltaic and Piezoelectric technologies are the most ready for short-term implementation, while Thermoelectric and WEC technologies show strong long-term potential despite facing technical and economic challenges. Hybrid combinations of multiple technologies have also been proven to enhance efficiency compared to single systems. The harvested energy can be utilized for various infrastructure needs, such as street lighting and Structural Health Monitoring (SHM) systems. This study recommends the application of hybrid technologies as a more efficient solution, tailored to the characteristics of the location and type of infrastructure. In addition, policy support and incentives are needed to accelerate the adoption of these technologies. By implementing these strategies, the construction industry can significantly contribute to achieving the UN's 2030 agenda for sustainable development.